Analysis of flow of polar and non polar incompressible ferrofluids (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper, flow between two parallel plates is analyzed for both polar and non polar ferrofluids. Velocity is obtained without pressure gradient for polar fluid and with pressure gradient for non polar fluid. The solution of the spin velocity is found in terms of applied magnetic field and magnetic flux density for polar fluid. Shear stress is calculated for both polar and non polar ferrofluid.